Polityka wschodnia Polski w nowych uwarunkowaniach - GIL, Andrzej (Historia i Świat, 2012)
The article addresses the need for a new methodology in Poland’s foreign policy. The need is driven by major changes which have taken place in Poland’s eastern neighbours. It seems that the ULB (Ukraine–Lithuania–Belarus) doctrine, born in the circles of the Parisian “Kultura” and regarded to be the foundations of Poland’s eastern policy is too alienated from the realities of the eastern part of Europe. Thus, it is important for Poland to take into account every new circumstance and to base its actions on concepts which are much better suited to the requirements of the contemporary world.